Kolaviron ameliorates chronic colitis induced by prolonged oral administration of Dextran Sulphate Sodium in Balb/c mice - Babajide O. Ajayi; Isaac A. Adedara; Onyediaka C. Emeka; Praise B. Awoyinka; Opeoluwa O. Beckley; Ademoyeje A. Adeleye; Ebenezer O. Farombi (Elsevier, 2022)
Ulcerative colitis is an idiopathic disease attributed to an aggressive dysregulated immune response that results in epithelial injury and diffuse inflammation in the colon. Ulcerative colitis may be acute or chronic with unpredictable relapse. Kolaviron, a bioflavonoid extracted from Garcinia kola has been reported to possess gastroprotective properties. We have previously reported the protective effect of kolaviron on acute colitis. This study investigated the effect of kolaviron on dextran sulphate sodium-induced chronic ulcerative colitis in Balb/c mice. Mice were randomly assigned to four groups of 10 mice each. Group I (Control) mice received corn oil at 2 ​ml/kg for forty-nine days. Group II mice received kolaviron at 200 ​mg/kg for forty-nine days. Group III mice received 3 cycles of dextran sulphate sodium (DSS) (2.5% w/v) in drinking water (each cycle is defined as 7 days of 2.5% DSS followed by 7 days of normal drinking water). Group IV received Kolaviron at 200 ​mg/kg body weight for 7 days before co-administration with 3 cycles of DSS (2.5% w/v). Administration of kolaviron significantly ameliorated increases in disease activity index in DSS-induced chronic ulcerative colitis in mice. Furthermore, kolaviron suppresses the expression of inducible nitric oxide synthase and cyclooxygenase-2 in DSS-treated mice. Additionally, kolaviron protected against colonic oxidant stress damage by augmenting the endogenous antioxidant with concomitant decrease in myeloperoxidase activity, tumor necrosis factor alpha, Interleukin-1β, and lipid peroxidation levels in DSS-treated mice. Moreover, kolaviron attenuated the disruption of the colonic histological architecture and reduced neutrophil infiltration in DSS-treated mice. In conclusion, kolaviron ameliorated DSS-induced chronic ulcerative colitis via antioxidant and anti-inflammatory mechanisms.